Intergenerational Queer Method(ologie)s: Dialogues in Literacy Research. Issue 1 (November 2022) - Coleman, James Joshua; Schey, Ryan; Blackburn, Mollie V.; Brochin, Carol; Cooper-Novack, Gemma; Crawley, S. Adam; Cruz, Cindy; Dutro, Elizabeth; Helton, Jack; Islam, Abdul-Qadir; Jiménez, Ileana; Lizárraga, José Ramón; et al.
Comprised of seven intergenerational dialogues, this article brings together emerging and established scholars to query into the future of queer literacy research. Addressing generational shifts in queer method(ologie)s, these dialogues advance epistemological, ontological, and ethical research quandaries related to queer and trans studies today. Holding implications for literacy research broadly, this article presents queer futurity as a research approach for addressing some of our field's most pressing concerns.